Coronavirus (COVID-19) Outbreak: A Most Fatal Pandemic in the Twenty First Century - Mohajan, Haradhan Kumar (Annals of Spiru Haret University. Economic Series, 2020)
The novel (new) coronavirus fatal disease (COVID-19) is an infectious disease caused by SARS-COV-2 (2019-nCoV). It has been identified as the causative agent of the viral pneumonia outbreak in Wuhan, China, at the end of 2019. It has a high human to human transmission capability and primarily targets the human respiratory system. Healthcare providers to common people are in high risks of the contamination of this fatal disease. It spreads person to person through respiratory droplets by coughs and sneezes. It is associated with severe and fatal respiratory disease in humans. At present it becomes great global public health concern. On 11 March 2020, the WHO declared the global COVID-19 outbreak as a pandemic. An attempt has been taken here to create consciousness among the common people to reduce the fatality of this killer disease.